Analysis of the Implementation of 21st-Century Skills Based on 2013 Curriculum in Primary Level - Karisma Anggun Surya; Ika Candra Sayekti; Siti Rahaimah binti Ali (Universitas Muhammadiyah Surakarta, 2022)
This study aimed to describe the integration of 21st-century skills in implementing the 2013 curriculum at an Indonesian Islamic Elementary School and the challenges and solutions associated with implementing 21st-century skills at the Islamic Elementary School. This study utilised a qualitative research and case study research design. Interviews and documentation were used to collect the data. Triangulation of methods and sources was utilised to validate data. In the meantime, data analysis was conducted using comparative analysis. The results of this study indicated that the integration and implementation of 21st-century skills at the Islamic Elementary School had been comprehensively carried out; however, several obstacles still need to be overcome. It is hoped that this research can serve as an overview of the implementation of 21st-century skills in schools so that any necessary improvements can be made to the learning process. This study implies that decision-makers in Indonesia should expand the knowledge and understanding of teachers regarding 21st-century skills. The current study reveals the implementation of 21st-century skills in primary education